Lifting the domestic cloak of silence: Resilient Australian women's reflected memories of their childhood experiences of witnessing domestic violence - Cohen, Lynne (2012)
Recognition is growing that childhood witnessing of domestic violence is tantamount to child abuse due to the damage the experience may have on the witnessing child’s long-term emotional and social wellbeing. This paper helps to lift the cloak of silence that surrounds the child witnessing phenomenon by presenting the recollected adult memories of six female former child witnesses. Utilizing a mixed case-study and consensual qualitative research design, the study’s findings reveal that the potential threat to a child witness’s immediate and long-term wellbeing can be mediated through the progressive development of a range of adaptive coping strategies. Of these, the strategy of establishing a safe place and a supportive relationship outside of the abusive nuclear family home seems pivotal to the witnessing child’s resilient ability to move on and lead a ‘rewarding’ adult life. The paper closes with a discussion on how the research findings can be progressed